The Influence of Turmeric and Curcumin on Female Reproductive Processes - Sirotkin, Alexander V. (Planta Medica, 2021)
The present review summarizes the available knowledge concerning the action of curcumin, the best-known polyphenol among the rhizomes of Curcumas, on female reproductive processes and their dysfunctions. Curcumin affects a number of physiological processes, including female reproduction (puberty, reproductive aging, ovarian follicullogenesis and oogenesis, and fecundity). Curcumin can affect these processes via changes in the release and reception of pituitary and ovarian hormones, growth factors and cytokines. Furthermore, it can influence the response of ovarian cells to these substances and external environmental factors. Finally, curcumin can affect oxidative processes within the ovary and numerous intracellular signalling pathways related to ovarian cell proliferation and apoptosis. These effects suggest the applicability of curcumin for stimulation of female reproductive processes in vivo and in vitro, as well as for the prevention, mitigation, and treatment of various reproductive disorders from ovarian insufficiency and infertility to polycystic ovarian syndrome and ovarian cancer.
Keywords: curcumin; turmeric; health; ovary; proliferation; apoptosis; hormone; fecundity